2m^2-5m+3=0

1 answer

To solve the quadratic equation 2m^2 - 5m + 3 = 0, we can use the quadratic formula:

m = (-b ± √(b^2 - 4ac)) / 2a

In our equation, a = 2, b = -5, and c = 3. Substituting these values into the quadratic formula:

m = (-(-5) ± √((-5)^2 - 4(2)(3))) / (2(2))
m = (5 ± √(25 - 24)) / 4
m = (5 ± √(1)) / 4

There are two possible solutions:
1. m = (5 + 1) / 4 = 6/4 = 3/2
2. m = (5 - 1) / 4 = 4/4 = 1

So the solutions to the quadratic equation 2m^2 - 5m + 3 = 0 are m = 3/2 and m = 1.